Karakteristik dan Uji Sensori Edible Cup dari Rumput Laut Eucheuma Cottonii - Indarti, Eti; Nafis, Azizul; Sulaiman, Muhammad Ikhsan (Agriculture Faculty, 2023)
The enormous use of plastic has a negative impact on environmental sustainability because the current plastic circulating is synthetic plastic that cannot be decomposed quickly in nature. To overcome this problem, the implementation of edible materials becomes necessary to reduce the use of less degradable plastic. Edible packaging on food ingredients is divided into several forms such as edible film, edible coating, encapsulation, and edible cups. Edible cup is one of the innovations in a cup-shaped wrap that can be safely and directly consumed. Edible cups can be produced from agricultural products that contain hydrocolloids such as seaweed. This study aims to produce edible cups from Euchuma cottonii seaweed and determine its characteristics. In this study, edible cups were made with the type of seaweed, namely Eucheuma cottonii with concentrations of 10%, 15%, and 20%. The resulting edible cup will then be subjected to a character, hedonic test and a description test. FTIR analysis show the character spectra of seaweed spectrum. The hardness of edible cup showed at concentration of 20% resulted the higher value (1.5 Kg/cm2), meanwhile the morphology of edible cup at 10% concentration showed the smooth surface. The hedonic test (color, aroma, and taste) on the edible cup showed that the concentration of 10% treatment exhibited the best edible cup with the most preferred hedonic score.